(untitled) (Medical Forum Monthly, 2024)
Objective: This work sought to identify the range of cardiac pathologies found in Down’s syndrome patients and establish the correlation existing between different pathologies and maternal age: a known risk factor for DS. Study Design: A purely descriptive cross sectional design Place and Duration of Study: This study was conducted at the Department of Pediatrics, Ayub Teaching Hospital Abbottabad from December 1, 2023 up to June 30, 2024. Methods: Down’s syndrome patient was determined by clinical presentation with reference to Hall’s criteria. The patients that met the inclusion criteria were selected for the study. The diagnostic test i-e echocardiography was performed in all the patients. All the collected data was entered and analyzed on Statistical Package for the Social Science (SPSS) version 23. Results: In this study the mean age of the patients was 31.97 ± 43.16 months, and sex distribution was having a male predilection of 0.9: 1. The mean value of maternal age of the patients was 34.28-year ± 5.18 years. In our study sample, the density of congenital heart disease variants was 54 of 70.12. Of all the congenital heart problem AVSD was the most prevalent in the study. Conclusion: Cardiac anomalies are especially present in Down syndrome, the prevalence of CHD ranges from 60-70% in this population with 70.12% in this study. The neonates might have different types of heart defect but with the most frequent being the AVSD. In addition, the occurrence of VSD is proportional to the rise in maternal age when the rest of the defe that were considered do not show any correlation with it.